Enhancing The Export Potential Of The Food Industry In Uzbekistan (Texas Journal of Multidisciplinary Studies, 2025)
Uzbekistan possesses significant potential for expanding its food industry exports. This paper examines the current state of the sector, identifies key challenges hindering export growth, and proposes strategies to enhance its competitiveness in international markets. Factors such as improving product quality and standards, modernizing production processes, strengthening supply chains, exploring new export markets, and attracting foreign investment are discussed. The role of government policies and support programs in fostering a conducive environment for export-oriented food businesses is also analyzed. This research contributes to a better understanding of the opportunities and challenges facing Uzbekistan's food industry and provides recommendations for unlocking its full export potential.